Imagens turísticas do Rio de Janeiro: memória, representação, identidade e sedução - Perrott, Isabella (2009)
Images participate of the construction of identities, imaginary and memories. Since travelling were been transforming into tourism, the image functioned in such a way as representation of unknown places, as memory for the experiences lived in a trip. This article analyses images that had participated of the construction of Rio de Janeiro as touristic destination, in the passage of 19th for the 20th century. Specifically, in advertisings of hotels and postcards of the port area.